COMPARATIVE EXPERIMENTAL STUDY OF MODAL PARAMETER ESTIMATION USING IBRAHIM TIME DOMAIN METHOD AND PEAK-PICKING METHOD - Anthony Sugianto, Yoel
Structural Health Monitoring is very important in knowing the actual condition of the structure during its operational period against damage that may occur to the structure. One of the methods used is through vibrations, where from these vibrations, modal parameters are obtained from time and frequency domain modal analysis. Time and frequency domain modal analysis itself has many methods, one of which is the Ibrahim Time Domain method as a time domain method and the Peak-Picking method as a frequency domain method. This study aims to test the reliability of the two modal analysis methods in determining the structural modal parameters, i.e. natural frequency and damping ratio, both under Experimental Modal Analysis (EMA) and Operational Modal Analysis (OMA) conditions.